A Large Laryngeal Mucocele Causing Progressive upper Airway Obstruction and Cervical Swelling - Aidonis, Ioannis; Lazaridis, Nikolaos; Piagkou, Maria; Anastasopoulos, Nikolaos; Natsis, Konstantinos (Acta medica (Hradec Kralove), 2017)
Laryngocele (LC) is an uncommon clinical entity, occasionally associated with fatal complications. If its neck becomes obstructed, mucous accumulates and then a laryngeal mucocele (LMC) is formed. Reports of LMCs are rare in the literature. A fluid-filled combined LMC in a 48 year-old Greek construction worker with presenting symptoms of cervical swelling and dysphonia is described. The male patient was surgically treated via an external approach. A LC rarely becomes symptomatic and infection unusually occurs. Magnetic resonance imaging depicts in detail the size, extension and structure of the neck mass and remains the diagnostic gold standard, providing superior soft-tissue discrimination, in cases of a concurrent laryngeal tumor. Histopathological examination confirms diagnosis, since there is always a high index of suspicion for malignancy. Established guidelines regarding surgical treatment of a LC do not exist. Although during the last two decades micro laryngoscopy with CO2 laser has gained popularity for the treatment of an internal LC, the external approach still remains the method of choice in cases of a combined LMC.
Keywords: Magnetic Resonance Imaging; Mucocele; výsledek terapie; Otorhinolaryngologic Surgical Procedures; Tomography, X-Ray Computed; lidé; Laryngeal Neoplasms; magnetická rezonanční tomografie; laryngoskopie; Treatment Outcome; cervical swelling; nádory hrtanu; Humans; disekce; otorinolaryngologické chirurgické výkony; external approach; Male; surgical treatment; laryngeal mucocele; Airway Obstruction; upper airway obstruction; počítačová rentgenová tomografie; lidé středního věku; obstrukce dýchacích cest; mužské pohlaví; mukokéla; Middle Aged; Laryngoscopy; Dissection